Radiation shielding glass having zinc-barium-borosilicate composition

A lead oxide-free zinc barium borosilicate glass composition, enhanced with bismuth, gadolinium, and cerium oxides, provides effective radiation shielding while maintaining transparency and safety, overcoming the limitations of traditional materials.

JP2025511419APending Publication Date: 2025-04-16グロク ホールディング ビーブイ
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024504167
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-12-02
Publication Date
2025-04-16

AI Technical Summary

Technical Problem

Existing radiation shielding materials, such as lead and heavy concrete, are toxic, lack transparency, and have limitations in neutron absorption and visibility, making them unsuitable for applications requiring transparency and safety from high-energy radiation.

Method used

A lead oxide-free zinc barium borosilicate glass composition is developed, incorporating additives like bismuth oxide, gadolinium oxide, and cerium oxide, which provides effective radiation shielding against x-rays, gamma rays, and neutrons while maintaining transparency and being environmentally friendly.

Benefits of technology

The glass composition effectively shields against high-energy radiation, ensuring transparency and safety, and is cost-effective and environmentally friendly, addressing the limitations of traditional radiation shielding materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511419000007
    Figure 2025511419000007
  • Figure 2025511419000001
    Figure 2025511419000001
  • Figure 2025511419000002
    Figure 2025511419000002
Patent Text Reader

Abstract

The present invention relates to a radiation shielding zinc-barium-borosilicate glass material produced from easily accessible, low-cost and abundantly available starting materials with a uniquely designed glass composition, particularly against X-rays and / or gamma rays and / or fast neutrons, etc. In particular, the use of a mixture of sodium oxide (Na2O), silicon dioxide (SiO2), boron oxide (BO3), calcium oxide (CaO), barium oxide (BaO), zinc oxide (ZnO), bismuth oxide (Bi2O3), gadolinium oxide (Gd2O3) and cerium oxide (CeO2) provides a satisfactory and effective shielding effect against X-rays and / or gamma rays and / or fast neutrons and / or neutrons and / or the like.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a radiation shielding glass comprising sodium oxide (Na2O), silicon dioxide (SiO2), boron oxide (BO3), calcium oxide (CaO), barium oxide (BaO), zinc oxide (ZnO), bismuth oxide (Bi2O3), gadolinium oxide (Gd2O3) and cerium oxide (CeO2) that can be used in the fields of aerospace and / or agriculture and / or sterilization according to the demands in the field of radiation shielding, especially in areas such as medical diagnostic centers equipped with equipment such as X-ray and / or PET / CT, involving scattering emitted from high level energy sources such as X-ray and / or gamma rays and / or neutrons and / or the like.

[0002] Known Prior Art With the recent technological development, the number of waves, rays and / or the like emitted from various sources such as electronic devices is increasing day by day. Such a situation can threaten human health in a negative way depending on the exposure time and the amount of exposure. In particular, high-energy radiation such as X-rays and / or gamma rays and / or neutron rays and / or the like can directly destroy the main bonds of living cells, causing harmful effects on human health. However, it can also cause health problems in the form of DNA mutations, dry eyes and skin burns. To reduce and / or eliminate these harmful health consequences, protective materials such as metal lead, concrete and / or the like are used.

[0003] Among the alternative materials that are often preferred to overcome radiation, lead materials are often preferred, but due to their toxic effects, they cause serious negative consequences for both humans and the environment.Furthermore, low neutron absorption capacity and lack of transparency are other drawbacks of lead-based materials.

[0004] Regarding the elimination of the destructive aspects of radiation-induced non-ionizing radiation, heavy concrete-based materials with various heavy aggregate loadings and various thickness factors are widely used to reduce high-energy scattering such as X-rays and / or gamma rays and / or neutrons and / or the like. However, the main technical problems are the changes in composition and the formation of phases due to factors such as time, temperature, etc. during application, as well as the risk of crack formation during operation. At the same time, due to its opaque appearance, it cannot be used for applications where visibility is essential.

[0005] Both metallic lead and heavy concrete materials are the main examples of known applications in the art. However, as mentioned above, their use is limited since they do not provide a transparent appearance. In particular, the above-mentioned materials cannot be used in the area of ​​access openings, which are mandatory within the framework of room design criteria. In view of this, various types of glasses are manufactured using various oxide compounds to reduce and / or eliminate the effects of high energy scattering, such as X-rays and / or gamma rays and / or neutrons and / or the like.

[0006] Lead oxide-based glass materials were first developed to reduce and / or eliminate the effects of high energy scattering, such as X-rays and / or gamma rays and / or neutrons. The high density (9.53 g / cm) provided by lead oxide compounds is 3 ) is intended to mitigate incident-emission scattering. However, while technically successful glasses have been produced, the toxic effects of lead oxide compounds on both human health and the environment have led to interest in alternative materials.

[0007] With regard to alternative glass systems, glass types such as tellurium oxide, germanium oxide, and vanadium oxide based glass types have been investigated in the literature but have not resulted in a commercial product due to limited availability of raw material sources, prohibitive costs, and the fact that the technology is not considered reasonable within known manufacturing methods.

[0008] There are studies on radiation shielding materials in the literature.

[0009] Patent application No. 2018 / 09709 relates to radiation shielding Er2O3 doped borosilicate glass, which can be used as glazing or cladding in buildings, as well as on the screens of radiation-emitting devices such as computers, mobile phones and televisions, where indicators of shielding performance were extracted as a result of doping with erbium oxide in varying proportions, and the doping with the best performance was found.

[0010] Patent application No. 2018 / 09707 lists radiation shielding CeO2-doped borosilicate glass as an invention. As a result of doping with cerium oxide in various proportions, indicators of shielding performance were extracted and the doping with the best performance was found.

[0011] European Patent Application No. EP1939147A1 relates to a radiation shielding glass and a method for producing the same. The glass composition contains, by weight, 10%-35% SiO2, 55%-80% PbO, 0%-10% B2O3, 0%-10% Al2O3, 0%-10% SrO, 0%-10% BaO, 0%-10% Na2O and 0%-10% K2O, and has a total light transmittance of 50% or more at a wavelength of 400 nm and a thickness of 10 mm. Another patent application US10035725B2 discloses an X-ray and gamma ray shielding glass and a method for producing such glass. The glass composition contains 0-35% by weight SiO2, 60-70% by weight PbO, 0-8% by weight B2O3, 0-10% by weight Al2O3, 0-10% by weight Na2O, 0-10% by weight K2O, 0-0.3% by weight As2O3, 0-2% by weight Sb2O3, 0-6% by weight BaO; and 0.05-2% by weight ZrO2. However, there is no information about zinc barium borosilicate glass materials in these documents.

[0012] To overcome the above-mentioned problems with alternative radiation shielding materials commercially and conventionally used in the art, there is a need for alternative glass compositions that are more cost-effective than readily available raw materials, provide protection against high energy scatter such as x-rays and / or gamma rays and / or neutrons and / or the like, and do not have harmful effects on humans and the environment.

[0013] As a result, the above-mentioned shortcomings and inadequacies of existing solutions have created a need for developments in the related art.

[0014] Object of the invention The present invention has been conceived by the inventor and aims to solve the above mentioned problems.

[0015] The primary objective of the present invention is to provide a lead oxide free zinc barium borosilicate glass composition specifically designed to protect against high energy scattering such as x-rays and / or gamma rays and / or neutrons and / or the like by minimizing the adverse effects on the environment and human health caused by lead oxide containing radiation shielding materials used in the art.

[0016] The object of the present invention is to provide an improved transparent zinc barium borosilicate glass material that has no harmful effects on humans and the environment. The glass material includes bismuth oxide (Bi2O3), gadolinium oxide (Gd2O3) and cerium oxide (CeO2).

[0017] A further object of the present invention is to develop a glass material that uses easily accessible raw materials, is cost effective and is highly compatible with forming processes.

[0018] For this purpose, a process for the production of zinc barium borosilicate glass was applied by selecting the following starting materials instead of the always preferred lead-based materials and / or glass-based and / or concrete containing various aggregates: colemanite, barite, silica sand, zinc oxide, soda ash, bismuth oxide, gadolinium oxide and cerium oxide. The use of colemanite, a calcium borate, is selected for its neutron capture and / or absorption and / or relaxation mediator properties.

[0019] In the present invention, it is preferred to use barite, a mineral made of barium sulfate, to mitigate X-rays and / or gamma rays and / or neutrons and / or the like. The use of zinc oxide is included to improve optical properties or improve radiation mitigation (attenuation) capabilities. Quartz sand, a source of silicon dioxide, is selected to provide structure for the glass system. Soda ash, made of sodium carbonate, is also preferred to lower the melting point of the glass system of the present invention.

[0020] In order to achieve the above-mentioned object, the present invention provides a radiation-shielding zinc-barium-borosilicate glass that can provide a transparent appearance in various places where radiation-induced ionizing radiation occurs, particularly in medical diagnostic centers and research institutes, and can also be used for the purpose of preventing harmful radiation from X-rays and / or gamma rays and / or fast neutron rays and / or the like, characterized in that it comprises adding gadolinium oxide (Gd2O3) and / or bismuth oxide (Bi2O3) and / or cerium oxide (CeO2) to zinc-barium-borosilicate (ZnO-BaO-B2O3-SiO2) glass powder.

[0021] The structural and characteristic features and all advantages of the present invention will be more clearly understood from the figures shown below and the detailed description written with reference to these figures, and an evaluation should be made in view of these figures and the detailed description. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1 is a schematic diagram of a manufacturing process for the radiation shielding zinc barium borosilicate glass material of the present invention.

[0023] Reference Description 1. Raw material formulation 2. Weighing unit 3. Raw material mixer 4.Melting furnace 5.Molding mold 6. Annealing furnace 7. Glassware DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] In this detailed description, preferred embodiments of the radiation shielding zinc-barium-borosilicate glass (ZnO—BaO—B 2 O 3 —SiO 2 ) of the present invention are described for the purpose of better understanding the subject matter only.

[0025] The present invention is a radiation shielding zinc-barium-borosilicate glass that can provide a transparent appearance in various locations where radiation-induced ionizing radiation may occur, particularly in medical diagnostic centers and research laboratories, and can also be used to prevent harmful emissions from X-rays and / or gamma rays and / or fast neutrons and / or the like, the zinc-barium-borosilicate (ZnO-BaO-B2O3-SiO2) glass containing the addition of gadolinium oxide (Gd2O3) and / or bismuth oxide (Bi2O3) and / or cerium oxide (CeO2). The glass is used in applications such as bone density measurement, mammography, dental X-ray, X-ray imaging, magnetic resonance (MR), PET / CT, gamma knife, as well as in the fields of space, defense, food and agriculture, among others, but not limited thereto.

[0026] The radiation-shielding glass contains 0.01 to 15 mol% Na2O, 0.01 to 5 mol% MgO, 0.01 to 5 mol% Al2O3, 15 to 75 mol% SiO2, 0.01 to 30 mol% B2O3, 0.01 to 13 mol% CaO, 0.01 to 35 mol% BaO, 0.01 to 2 mol% TiO2, 0.01 to 5 mol% SrO, 0.01 to 15 mol% ZnO, 0.01 to 4 mol% Li2O, 0.01 to 10.00 mol% Gd2O3, 0.01 to 10 mol% Bi2O3, 0.01 to 10 mol% CeO2, 0.01 to 5 mol% Sb2O3, and 0.001 to 0.10 mol% Fe2O3 as component range values.

[0027] The radiation-shielding glass of the present invention has a melting temperature value of more than 1000° C. and less than 1400° C., and an initial annealing temperature value of more than 400° C. and less than 700° C. Also, it has an annealing time in the range of 80 to 120 minutes.

[0028] The thickness of the radiation-shielding glass of the present invention is in the range of 3 to 100 mm. The glass density is 3.25 g / cm 3 and higher, and Young's modulus is 75GPa and higher. The diffraction coefficient of the above radiation shielding glass is 1.76 and higher. The thermal expansion coefficient is at most 8.75x10 -6 / K.

[0029] The above radiation shielding glass shall have the following dimensions and numbers regarding the number of gas inclusions (bubbles, cracks, and / or wrinkles):

[0030] - 15 pieces per 30 grams of glass with a diameter of 0.001-0.01 mm - 10 pieces per 30 grams of glass with a diameter of 0.01-0.1 mm, - diameter - 5 pieces per 30 grams of glass of 0.1 mm and above. The subject of the present invention is a radiation shielding glass having a transmission of 50% and more at a wavelength of 400 nm and a thickness of at least 10 mm, and a transmission of 75% and more at a wavelength of 550 nm and a thickness of at least 10 mm.

[0031] The radiation-shielding glass of the present invention contains, as starting materials, silica sand, quartz, silica stone, barite, barium carbonate, colemanite, ulexite, soda ash, albite, limestone, dolomite, spodumene, sodium nitrate, sodium sulfate, zinc oxide, gadolinium oxide, gadolinium sulfate, bismuth oxide, bismuth nitrate, cerium oxide, antimony trioxide, strontium carbonate, anthracite, zinc selenite, and cobalt oxide.

[0032] To prepare glass blends, the chemical composition of raw materials is very important. Therefore, the present invention uses high purity raw materials with satisfactory chemical composition characteristics. High purity here means at least 99.00% main components and maximum 1000ppm Fe2O3. The raw materials are carefully weighed within limited tolerances. Depending on the given amount of each raw material, the glass tolerance is set to maximum 0.01% of the weighed amount.

[0033] Impurities such as Fe2O3 (iron oxide) and / or similar impurities (e.g., Cr2O3) in the raw materials used in the glass manufacturing process can cause problems such as coloration of the melt or similar (e.g., bubbles) glass defects. The transparency of the glassware is important for effective radiation shielding, and the amount of iron oxide controls the resulting coloration; that is, iron oxide causes a natural coloration of the glass through a greenish tint, which results in poor visibility. To produce glassware that can provide adequate transparency, it is desirable to have the amount of iron oxide not exceed 1000 ppm.

[0034] Furthermore, transparent glassware runs the risk of having some defects that are visually evident, including scratches, bubbles, or the like. To achieve superior quality in glassware, it is important to remove the imperfections.

[0035] Density is an important parameter that is monitored in a specific way and is the result of optimizing the proprietary mixture. The higher the density of the glass system, the better the performance of the shielding glass. The densities obtained by varying the glass composition are generally in the range of 2.75 - 3.00 g / cm.3 More than 3.00 to 3.25 g / cm 3 , more preferably 3.25 to 3.50 g / cm 3 , optimally 3.50g / cm 3 As a result of this study, the density of glass is estimated to be 3.25 g / cm 3 It turned out to be super.

[0036] The radiation-shielding glass material of the present invention is composed of 0.01 to 15.00 mol% Na2O, 0.01 to 5.00 mol% MgO, 0.01 to 5.00 mol% Al2O3, 15.00 to 75.00 mol% SiO2, 0.01 to 30 mol% B2O3, 0.01 to 13 mol% CaO, 0.01 to 35 mol% BaO, 0.01 to 2.00 mol% TiO2, 0.01 to 5 The novel glass composition includes molar percentages ranging from 0.00 mol% SrO, 0.01-15.00 mol% ZnO, 0.01-4.00 mol% Li2O, 0.01-10.00 mol% Gd2O3, 0.01-10.00 mol% Bi2O3, 0.01-10 mol% CeO2, 0.01-5 mol% Sb2O3, and 0.001-0.10 mol% Fe2O3. Additionally, a refining agent of cerium oxide ranging from 100-5,000 ppm can be used to remove glass defects such as cords, bubbles, or similar. In the present invention, other toxic refiners such as arsenic trioxide or similar are not preferred. Additionally, the amount of iron oxide, which naturally causes a greenish color in glassware and also reduces visibility, is strictly controlled in the melting process of the raw material mixture.

[0037] Sodium dioxide is a component that increases the moldability of the glass composition and at the same time lowers the melting point. The content of sodium dioxide is 0 to 15 mol%, preferably 5 to 10 mol%, and more preferably 10 to 15 mol%. If the content of sodium dioxide exceeds 15 mol%, the high temperature viscosity becomes uncontrollable, resulting in insufficient radiation blocking ability.

[0038] Silicon dioxide is the structure of the glass composition and also the main network former of the present invention. The content here is 15-75 mol%, preferably 55-60 mol%, more preferably 60-75 mol%. If the content of silicon dioxide exceeds 75 mol%, the melting point of the glass composition increases, resulting in uncontrollable viscosity characteristics. Conversely, if the amount of silicon dioxide is lower than 15 mol%, the network formation becomes thermally unstable.

[0039] Boron oxide is a component that not only lowers the melting point of the glass composition, but also enhances the thermal stability of the glass structure by appropriately changing its structure under appropriate conditions. The content of boron oxide is between 0 and 30 mol%, preferably between 0.1 and 5 mol%, more preferably between 5 and 10 mol%. If the content of boron oxide is much higher than 30 mol%, the thermal stability of the glass article will be deteriorated.

[0040] Calcium oxide is a component that enhances the chemical resistance, especially water resistance, of the glass composition. The calcium oxide content is between 0 and 13 mol%, preferably between 0.1 and 4 mol%, more preferably between 4 and 13 mol%. If the calcium oxide content exceeds 13 mol%, formability becomes difficult and, as a result, the radiation barrier against X-rays and / or gamma rays and / or fast neutrons and / or the like is insufficient.

[0041] Barium oxide is a preferred component for increasing the radiation exposure capability of glass materials due to the barium element having a high atomic number. The barium oxide content is 0 to 35 mol%, preferably 0.1 to 15 mol%, and more preferably 15 to 35 mol%. If the barium oxide content exceeds 30 mol%, the glass becomes thermally unstable.

[0042] Zinc oxide is a component that improves the glass-forming ability and provides higher ultraviolet transparency. The zinc oxide content is 0 to 15 mol%, preferably 0.1 to 4 mol%, more preferably 4 to 8 mol%, and even more preferably 8 to 12 mol%. If the zinc oxide content exceeds 15 mol%, the radiation shielding performance of the glass is adversely affected.

[0043] Gadolinium oxide is used as a barrier against X-rays and / or gamma rays and / or fast neutrons and / or the like. Due to its high density value, it improves radiation shielding properties. The content of gadolinium oxide is 0-10 mol%, preferably 0.1-1 mol%, more preferably 1-3 mol%, more preferably 3-6 mol%. If the content of gadolinium oxide is more than 10 mol%, the transparency is impaired with respect to the color of the glass.

[0044] Bismuth oxide is a component that improves the radiation protection performance of glass by using bismuth element with a high atomic number. The content of bismuth oxide is 0 to 10 mol%, preferably 0.1 to 1 mol%, more preferably 1 to 3 mol%, and even more preferably 3 to 6 mol%. If the content of bismuth oxide exceeds 10 mol%, the glass becomes thermally unstable.

[0045] Cerium oxide is a component used as a fining agent in glass systems. The content of cerium oxide is 1,000 to 5,0000 ppm, preferably 1,000 to 3,000 ppm. If the content of cerium oxide is less than 1,000 ppm, the purification of glassware becomes insufficient, resulting in the inclusion of bubbles due to the glassware.

[0046] As long as the properties of the glass are not impaired, any other component (eg, Li2O, K2O) can be added up to 10 mol %.

[0047] Examples of Glasses of the Invention In practical embodiments of the improved glass compositions, specifically designed for the attenuation of X-rays and / or gamma rays and / or fast neutrons and / or the like, the following blend mixtures are prepared in mole percentages. These blends may vary depending on the chemical properties of the raw materials selected within the scope of the present invention. The utilization of raw materials in terms of the amounts obtained, both chemical and physical, may vary within a given tolerance range.

[0048] Figure 1 shows the manufacturing process diagram. First, the selected raw materials are prepared to have the glass composition described in each different application and sub-formulation. The weighing is performed according to the listed tolerance rate. After weighing each compound, alumina balls are placed in a porcelain container, and the mixing process is carried out in a mill and / or mechanical mixer in a dry environment at a rotation speed of 250-500 rpm for 15-60 minutes to form a homogeneous mixture. After obtaining a homogeneous mixture, the prepared glass stack is melted in an electric resistance lift type melting furnace and / or a gold-platinum alloy crucible without any atmosphere control. The melting temperature can be selected at any temperature value between 1000 and 1400°C. The holding time at the melting temperature is 60-180 minutes. Once the glass melt is obtained and the waiting time is over, the glass melt is preferably poured immediately into a graphite mold or placed in a gold-platinum alloy crucible at room temperature for 5-10 minutes. The glass product obtained by both methods is then removed from the mold containing the glass melt or from the gold-platinum alloy crucible and placed in an annealing furnace heated to any temperature between 400 and 700°C for any time between 80 and 120 minutes for stress relief annealing, and after completion of the waiting period the glass product is removed from the annealing vessel and / or furnace to obtain the final glass product.

[0049] In Table 1 below, Example 1: Glass composition for effectively blocking radiation such as X-rays and / or gamma rays and / or fast neutrons and / or the like is provided. The designation OR represents the base formula. The designation BA indicates an increased amount of barium oxide (BaO). The designation BO relates to an increased amount of boron oxide (B2O3). Increasing both BaO and B2O3 improves the mitigation capability of the base glass formulation, OR glass, against X-rays and / or gamma rays and / or fast neutrons and / or the like. Table 1: Example 1: Glass composition for effectively blocking radiation such as X-rays and / or gamma rays and / or fast neutrons and / or the like [Table 1] First, the selected raw materials are prepared to have the glass composition described in each different application and sub-formulation. The weighing is performed according to the listed tolerance rate. After weighing each compound, alumina balls are placed in a porcelain container, and a mixing process is carried out using a mill and / or mechanical mixer in a dry medium at a rotation speed of 250-500 rpm for 15-60 minutes to form a homogeneous mixture. After obtaining a homogeneous mixture, the prepared glass stack is placed in a gold-platinum alloy crucible and melted in an electric resistance box type and / or lift type melting furnace without atmosphere control. The melting temperature is any temperature between 1000 and 1400°C. As the waiting time at the melting temperature, any temperature value between 60 and 180 minutes is selected. Once the glass melt is obtained and the waiting time of the melt is over, the glass melt is preferably poured immediately into a graphite mold or kept in a gold-platinum alloy crucible at room temperature for 5-10 minutes to obtain a glass product. The glass product obtained by both methods is then removed from the mould containing the glass melt or from the gold-platinum alloy crucible and placed in an annealing furnace heated to any temperature between 400 and 700°C for any period between 80 and 120 minutes for stress relief annealing, and after completion of the waiting time, the glass product is removed from the annealing vessel and / or furnace to successfully obtain the final glass product.

[0050] In the case of the concrete composition of Example 1, the radiation shielding glass has a radiation intensity of 0.217 cm at an energy level of 662 keV. -1 and linear attenuation coefficient values ​​above that, 0.155 cm at the energy level of 1173 keV -1 and linear attenuation coefficient values ​​above 0.150 cm at the 1332 keV energy level. -1 and greater linear attenuation coefficient values.

[0051] In Table 2 below, Example 2: Glass composition for effectively blocking radiation such as X-rays and / or gamma rays and / or fast neutrons and / or the like is shown. The symbol BB stands for the base formula. The symbol BBGd stands for the amount of gadolinium oxide (Gd2O3) added. The symbol BBBi stands for the amount of bismuth oxide (Bi2O3) added. The symbol BBCe stands for the amount of cerium oxide (CeO2) added. The addition of Gd2O3, Bi2O3 and CeO2 improves the mitigation ability of the base glass formula BB glass against X-rays and / or gamma rays and / or fast neutrons and / or the like. Table 2 Example 2: Glass composition for effectively blocking radiation such as X-rays and / or gamma rays and / or fast neutrons and / or the like [Table 2] First, the selected raw materials are prepared to have the glass composition described in each different application and sub-formulation. The weighing is performed according to the listed tolerance rate. After weighing each compound, alumina balls are placed in a porcelain container, and a mixing process is carried out in a mill and / or mechanical mixer in a dry environment at a rotation speed of 250-500 rpm for 15-60 minutes to form a homogeneous mixture. After obtaining a homogeneous mixture, the prepared glass stack is melted in an electric resistance lift type melting furnace and / or a gold-platinum alloy crucible without atmosphere control. The melting temperature is selected at any temperature between 1000 and 1400°C. The waiting time at the melting temperature is selected between 160 and 180 minutes. Once the glass melt is obtained and the waiting time of the melt is over, the glass melt is preferably immediately poured into a graphite mold or kept in a gold-platinum alloy crucible at room temperature for 5-10 minutes to obtain a glass product. The glass products obtained by both methods are then removed from the mould containing the glass melt or from the gold-platinum alloy crucible and placed in an annealing furnace heated to any temperature between 400 and 700°C for any time between 80 to 120 minutes for stress relief annealing, and after completion of the waiting time, the glass products are removed from the annealing vessel and / or furnace to successfully obtain the final glass product.

[0052] The radiation-shielding glass of the present invention, in the case of the embodiment of Example 2, has a radiation intensity of 0.254 cm at an energy level of 662 keV. -1 and linear attenuation coefficient values ​​above that, 0.175 cm at the energy level of 1173 keV -1 and linear attenuation coefficient values ​​above that, 0.165 cm at the energy level of 1332 keV -1 and greater linear attenuation coefficient values.

[0053] In Table 3 below, Example 3: Glass composition for effectively blocking radiation such as X-rays and / or gamma rays and / or fast neutrons and / or the like is shown. The symbols BBGd1, BBGd2 and BBGd3 represent increasing amounts of gadolinium oxide (Gd2O3). Increasing Gd2O3 improves the mitigation ability against X-rays and / or gamma rays and / or fast neutrons and / or the like. Table 3 Example 3: Glass composition for effectively blocking radiation such as X-rays and / or gamma rays and / or fast neutrons and / or the like [Table 3] The linear attenuation coefficient (μ) values ​​obtained in Examples 1, 2, and 3 are expressed in cm -1 The units are shown in Tables 4, 5 and 6. Three different gamma ray energy levels, 662, 1173 and 1332 keV, were selected as the energy levels of the samples. Gamma ray spectrometry was used within the scope of the measurement method. NaI was used as the detector. Co60 and Cs137 were selected as the radiation sources. Table 4: Linear attenuation (μ) values ​​(cm) at 662, 1173 and 1332 keV in Example 1 -1 ). [Table 4] Table 5 Linear attenuation (μ) values ​​(cm) at 662, 1173 and 1332 keV in Example 2 -1 ) [Table 5] Table 6: Linear attenuation coefficient (μ) values ​​(cm) at 662, 1173 and 1332 keV in Example 3 -1 ) [Table 6]

Claims

1. In radiation shielding zinc-barium-borosilicate glass, which can provide a transparent appearance and can also be used to prevent harmful radiation from X-rays and / or gamma rays and / or fast neutrons and / or the like in various places where radiation-induced ionizing radiation occurs, particularly in medical diagnostic centers and research institutes, zinc-barium-borosilicate (ZnO-BaO-B 2 O 3 -SiO 2 ) Glass powder with gadolinium oxide (Gd 2 O 3 ) and / or bismuth oxide (Bi 2 O 3 ) and / or cerium oxide (CeO 2 ) is added to a radiation shielding zinc-barium-borosilicate glass.

2. 0.01 to 15 mol% Na 2 O, 0.01 to 5 mol % MgO, 0.01 to 5 mol % Al 2 O 3 , 15 to 75 mol % of SiO 2 , 0.01 to 30 mol% B 2 O 3 , 0.01 to 13 mol% CaO, 0.01 to 35 mol% BaO, 0.01 to 2 mol% TiO 2 , 0.01 to 5 mol% SrO, 0.01 to 15 mol% ZnO, 0.01 to 4 mol% Li 2 O, 0.01 to 10.00 mol% Gd 2 O 3 , 0.01 to 10 mol% Bi 2 O 3 , 0.01 to 10 mol% of CeO 2 , 0.01 to 5 mol% Sb 2 O 3 and 0.001 to 0.10 mol% Fe 2 O 3 2. The radiation shielding zinc-barium-borosilicate glass of claim 1, comprising a range of values ​​of components:

3. 10. The radiation shielding zinc-barium-borosilicate glass of claim 1 for use in applications such as, but not limited to, bone density measurement, mammography, dental x-ray, x-ray imaging, magnetic resonance imaging (MRI), PET / CT, gamma knife, and in space, defense, food and agriculture fields.

4. Fe 2 O 3 and Cr 2 O 3 2. The radiation shielding zinc-barium-borosilicate glass of claim 1, wherein the components have values ​​of 1000 ppm or less.

5. 2. The radiation shielding zinc-barium-borosilicate glass of claim 1, having a melting temperature greater than 1000°C and less than 1400°C.

6. 2. The radiation shielding zinc-barium-borosilicate glass of claim 1 having an initial annealing temperature greater than 400°C and less than 700°C.

7. The radiation shielding zinc-barium-borosilicate glass of claim 1, wherein the annealing time is in the range of 80 to 120 minutes.

8. 2. The radiation shielding zinc-barium-borosilicate glass of claim 1, wherein the glass thickness is in the range of 3 to 100 mm.

9. 2. The radiation shielding zinc-barium-borosilicate glass of claim 1 having a number of gas inclusions (blisters and / or bubbles) of 15 per 30 grams of glass with a diameter between 0.001 and 0.01 mm, 10 per 30 grams of glass with a diameter between 0.01 and 0.1 mm, and 5 per 30 grams of glass with a diameter of 0.1 mm and above.

10. Glass density is 3.25 g / cm 3 10. The radiation shielding zinc-barium-borosilicate glass of claim 1 , wherein the zinc-barium-borosilicate glass has a thickness of 100 nm or more.

11. 2. The radiation shielding zinc-barium-borosilicate glass of claim 1, having a Young's modulus value of 75 GPa and above.

12. 2. The radiation shielding zinc-barium-borosilicate glass of claim 1, having a refractive index of 1.76 and above.

13. 2. The radiation shielding zinc-barium-borosilicate glass of claim 1, having a transmission of 50% or more at a wavelength of 400 nm and a thickness of at least 10 mm.

14. 2. The radiation shielding zinc-barium-borosilicate glass of claim 1, having a transmission of 75% or greater at a wavelength of 550 nm and a thickness of at least 10 mm.

15. Thermal expansion coefficient is 8.75x10 -6 2. The radiation-shielding zinc-barium-borosilicate glass of claim 1, wherein the glass has a viscosity of 1.0 μm / K or less.

16. Component Na 2 O, SiO 2 , B 2 O 3 , CaO, BaO, ZnO, MgO, Al 2 O 3 , SrO and Fe 2 O 3 In the case of 0.217 cm at the energy level of 662 keV -1 2. The radiation shielding zinc-barium-borosilicate glass of claim 1 having a linear attenuation coefficient value of and above.

17. Component Na 2 O, SiO 2 , B 2 O 3 , CaO, BaO, ZnO, MgO, Al 2 O 3 , SrO and Fe 2 O 3 In the case of 0.155 cm at the energy level of 1173 keV -1 2. The radiation shielding zinc-barium-borosilicate glass of claim 1 having a linear attenuation coefficient value of and above.

18. Component Na 2 O, SiO 2 , B 2 O 3 , CaO, BaO, ZnO, MgO, Al 2 O 3 , SrO and Fe 2 O 3 In the case of 0.150 cm at the energy level of 1332 keV -1 2. The radiation shielding zinc-barium-borosilicate glass of claim 1 having a linear attenuation coefficient value of and above.

19. Component Na 2 O, SiO 2 , B 2 O 3 , CaO, BaO, ZnO, MgO, Al 2 O 3 , SrO, Fe 2 O 3 , Gd 2 O 3 , Bi 2 O 3 and CeO 2 In the case of 0.254 cm at the energy level of 662 keV -1 2. The radiation shielding zinc-barium-borosilicate glass of claim 1 having a linear attenuation coefficient value of and above.

20. Component Na 2 O, SiO 2 , B 2 O 3 , CaO, BaO, ZnO, MgO, Al 2 O 3 , SrO, Fe 2 O 3 , Gd 2 O 3 , Bi 2 O 3 and CeO 2 In the case of 0.175 cm at the energy level of 1173 keV -1 2. The radiation shielding zinc-barium-borosilicate glass of claim 1 having a linear attenuation coefficient value of and above.

21. Component Na 2 O, SiO 2 , B 2 O 3 , CaO, BaO, ZnO, MgO, Al 2 O 3 , SrO, Fe 2 O 3 , Gd 2 O 3 , Bi 2 O 3 and CeO 2 In the case of 0.165 cm at the energy level of 1332 keV -1 2. The radiation shielding zinc-barium-borosilicate glass of claim 1 having a linear attenuation coefficient value of and above.

22. Component Na 2 O, SiO 2 , B 2 O 3 , CaO, BaO, ZnO, MgO, Al 2 O 3 , SrO, Fe 2 O 3 and Gd 2 O 3 In the case of 0.302 cm at the energy level of 662 keV -1 2. The radiation shielding zinc-barium-borosilicate glass of claim 1 having a linear attenuation coefficient value of and above.

23. Component Na 2 O, SiO 2 , B 2 O 3 , CaO, BaO, ZnO, MgO, Al 2 O 3 , SrO, Fe 2 O 3 and Gd 2 O 3 In the case of 0.206 cm at the energy level of 1173 keV -1 2. The radiation shielding zinc-barium-borosilicate glass of claim 1 having a linear attenuation coefficient value of and above.

24. Component Na 2 O, SiO 2 , B 2 O 3 , CaO, BaO, ZnO, MgO, Al 2 O 3 , SrO, Fe 2 O 3 and Gd 2 O 3 In the case of 0.171 cm at the energy level of 1332 keV -1 2. The radiation shielding zinc-barium-borosilicate glass of claim 1 having a linear attenuation coefficient value of and above.

25. 25. The radiation shielding zinc-barium-borosilicate glass according to any one of claims 1 to 24, having as starting materials silica sand, quartz, silica stone, barite, barium carbonate, colemanite, ulexite, soda ash, albite, limestone, dolomite, spodumene, sodium nitrate, sodium sulfate, zinc oxide, gadolinium oxide, gadolinium sulfate, bismuth oxide, bismuth nitrate, cerium oxide, antimony trioxide, strontium carbonate, anthracite, zinc selenite, and cobalt oxide.

Citation Information

Patent Citations

  • Lead-free electric light source glass tube and preparation method thereof

    CN106277759A

  • Radiation shielding glass

    JP1998226533A

  • Glass substrate for field emission display

    JP2003054985A

  • Panel for cathode-ray tube

    JP2004146094A

  • Radiation shielding glass

    WO2007043280A1